The InterPro protein families and domains database: 20 years on. Issue Volume 49:Issue D1(2021) (6th November 2020) - Blum, Matthias; Chang, Hsin-Yu; Chuguransky, Sara; Grego, Tiago; Kandasaamy, Swaathi; Mitchell, Alex; Nuka, Gift; Paysan-Lafosse, Typhaine; Qureshi, Matloob; Raj, Shriya; Richardson, Lorna; Salazar, Gustavo A; et al.
Abstract: The InterPro database (https://www.ebi.ac.uk/interpro/ ) provides an integrative classification of protein sequences into families, and identifies functionally important domains and conserved sites. InterProScan is the underlying software that allows protein and nucleic acid sequences to be searched against InterPro's signatures. Signatures are predictive models which describe protein families, domains or sites, and are provided by multiple databases. InterPro combines signatures representing equivalent families, domains or sites, and provides additional information such as descriptions, literature references and Gene Ontology (GO) terms, to produce a comprehensive resource for protein classification. Founded in 1999, InterPro has become one of the most widely used resources for protein family annotation. Here, we report the status of InterPro (version 81.0) in its 20th year of operation, and its associated software, including updates to database content, the release of a new website and REST API, and performance improvements in InterProScan.